KEMAMPUAN NUMBER SENSE SISWA SD DITINJAU DARI PERBEDAAN JENIS KELAMIN DI BUKITTINGGI - Dara Septa Wahyuni; Duryati Duryati (Universitas Negeri Padang, 2019)
The ability of number sense students in terms of gender differences.This study aims to determine differences in the ability of number sense students in term of gender differences in Bukittinggi. The designof this study was comparative quantitative, with the study population being fifth grad studentsat Bukittinggi City Elementary School. The research sample of 97 people with a purposive sampling cluster technique. Data collection was carried out using a number sense test measuring instrument developed by Mcntosh, etal, which a mounted to 22 questions. The data analysis technique used is the different t-test. The results obtained p value = 0.135 (p> 0.05) and a t value of 1.442 significant at the 0.05 level, which means that there is no significant difference in the ability of the number sense students of gender.Kemampuan number sense siswa SD ditinjau dari perbedaan jenis kelamin. Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan number sense siswa ditinjau dari perbedaan jenis kelamin di Bukittinggi. Desain penelitian ini adalah kuantitatif komperatif, dengan populasi penelitian yaitu siswa kelas V SD Kota Bukittinggi. Sampel penelitian berjumlah 97 orang dengan teknik cluster purposive sampling. Pengumpulan data dilakukan dengan menggunakan alat ukur number sense test yang dikembangkan oleh Mclntosh, et.al yang berjumlah 22 soal. Teknis analisis data yang digunakan adalah uji beda t-test. Hasil penelitian didapatkan nilai p=0,135 (p>0,05) dan nilai t sebesar 1,442 signifikan pada taraf 0.05, yang berarti tidak terdapat perbedaan kemampuan number sense siswa yang signifikan dari jenis kelamin.